Improving Studentsâ VocabularyMasteryThrough Cartoon Movie at the Grade Fifth Students of SDN 016 Rambah Samo. - Handayani, Dwi Astuti; Rasyidah, Ummi; Kasyulita, Evi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research is conducted to improve studentsâ vocabulary mastery at fifth grade of Elementary school 016 Rambah Samotrought Cartoon movie. This research used Classroom Action Research (CAR) which conducted to solve the studentsâ problem in Vocabulary Mastery. This research conducted in two cycles, in every cycle consist of plan, action, observation and reflection. The data were gathered through qualitative and quantitative data. The finding of this research indicated that the implementation of cartoon movie was successful since there an improvement ofstudents vocabulary mastery. Based on the finding mentioned, the researcher suggests that English teacher could implement cartoon movie media in teaching English vocabulary mastery.